Políticas públicas e os espaços democráticos: um olhar sobre a III Conferência Nacional de Segurança Alimentar e Nutricional - Brasil - Silvia A. Zimmermann (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2008)
SMF started the process of meetings of the Brazilian Civil Society, which consolidated the democratic transition. Then, it multiplied the schedule of conferences, forums and meetings of local/national councils. These spaces assure the approximation between the State and the Civil Society, guarantee the recognition of excluded categories and the strengthening of these categories, as well as the identification of new categories. In Brazil, there are many participation spaces, and the Conferences specially mobilize several sections and propose the agreement of public policies. However, how do the democratic process and the assurance of the represented groups´ craving express itself in Conferences? How does the process of construction of the public policy happen before the opinion diversity? Afterwards, a reflection about the Conferences is made, using, as a reference, the III National Conference on Food and Nut ritional Security, Fortaleza, 2007. The number of participants who attended this event was 1,800 people: 1,333 were deputies from the civil and the federal and local governmental society; 360 national participants and 70 international participants from 23 countr ies. The data suggest a degree of complexity of glances and perceptions in the discussion of the same policy, as well as in the recognition and assurance of the cravings of the present representations.